Effect of dexmedetomidine infusion on N-terminal pro-B-type natriuretic peptide level in patients with femoral shaft fractures under general anesthesia - Mirkheshti, Alireza; Memary, Elham; Shafiee, Hamed; Dahi, Mastaneh (Bangladesh Journal of Pharmacology, 2016)
This study was performed to assess the effect of dexmedetomidine on the level of N-terminal proB-type natriuretic peptide (NT-pro-BNP) in patients undergoing major orthopedic surgery. Patients undergoing general anesthesia for femoral shaft fracture surgery were randomly assigned to either 0.5 µg/kg/hour dexmedetomidine or normal saline. Changes in levels of NT-pro-BNP and hemodynamic parameters were compared. Data of 46 patients were analyzed and it was found that the change in NT-pro-BNP levels in the dexmedetomidine group was significantly less than the control group (p = 0.001). In addition, bleeding, changes in systolic and diastolic blood pressure in dexmedetomidine group was significantly less than the control group (p?0.001). It is likely that dexmedetomidine infusion can reduce the rise of NTpro-BNP level and therefore is associated with better cardiac outcome. In addition, dexmedetomidine infusion can achieve hemodynamic stability in femoral shaft fracture under general anesthesia.